2005
DOI: 10.1016/j.ygyno.2005.01.013
|View full text |Cite
|
Sign up to set email alerts
|

DCS liquid-based system is more effective than conventional smears to diagnosis of cervical lesions

Abstract: This study confirms the superiority of the liquid-based cytology system DCS to detect cervical lesions. The rate of adequate DSC slides was significantly higher than with conventional cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…This study showed that the LBC method resulted in a significantly lower percentage of unsatisfactory specimens than the conventional method. Many prior reports have suggested that the LBC method produces a lower percentage of unsatisfactory specimens [1,2,3,4,5,6,7,8,9,10]. In studies reporting no difference in the reduction of unsatisfactory specimens, the rates were lower than those in a meta-analysis [16] and other reports (LBC method 0.3% vs. conventional method 1.1%) [17].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This study showed that the LBC method resulted in a significantly lower percentage of unsatisfactory specimens than the conventional method. Many prior reports have suggested that the LBC method produces a lower percentage of unsatisfactory specimens [1,2,3,4,5,6,7,8,9,10]. In studies reporting no difference in the reduction of unsatisfactory specimens, the rates were lower than those in a meta-analysis [16] and other reports (LBC method 0.3% vs. conventional method 1.1%) [17].…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the Bethesda system (TBS; 2001), which outlines cytological diagnostic criteria for cervical smears, is only gradually being adopted. It has been reported that the liquid-based cytology (LBC) method is useful for reducing the number of unsatisfactory specimens [1,2,3,4,5,6,7,8,9,10]. Unsatisfactory specimens are ≤1.1%, and one of the most common reasons for unsatisfactory specimens was too few squamous cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, when LBC and conventional smears have been measured against a biopsy-proven result, the differences have not shown significant improvements in terms of ameliorated performance in other reports from developed countries [10]. However, this assumption is not necessarily true for poorer settings [1]. The reasons for these discrepancies could be attributed to several factors, and most of those factors have been discussed previously.…”
Section: Discussionmentioning
confidence: 98%
“…The impassioned disputes between defenders of conventional Pap smears and those who believe in the supremacy of liquid-based cytology (LBC) are generally supported by the belief that one of these methods has the potential to detect more cases of high-grade squamous intraepithelial lesions (HSILs) on routine screenings for cervical cancer even in high-risk settings [1]. Moreover, LBC is believed to improve the quality of sample preparations, be more cost-effective, allow the use of computer-assisted screening and provide residual material for ancillary testing, including human papillomavirus (HPV) testing, all of which strongly favor the use of LBC [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…If ASC-US and ASC-H are not taken into consideration, the LSIL + HSIL proportions for LBC remain twice that of CPT (1.1 vs. 0.5%). Among high-risk Brazilian women, LBC has been shown to outperform CPT [9]; however, its superiority has not been borne out among low-risk women [9,10,11,12]. Nonetheless, in the setting of a community whose population numbers in the millions, small proportional differences equate to significant differences among actual patients.…”
Section: Discussionmentioning
confidence: 99%